How to improve lumbar puncture uptake in children: a guide to healthcare professionals - Anuar, Muhamad Azamin; Abu Bakar, Asrar (Malaysian Paediatric Association, 2025)
Lumbar puncture (LP) is a medical procedure in which a thin needle is inserted into the lower part of the spinal canal to collect cerebrospinal fluid for diagnostic or therapeutic purposes. LP is vital for diagnosing serious paediatric conditions, yet refu sal rates vary globally from 80% in Kuwait to 5% in the US [1]. Barriers include parental fears of pain or paralysis, clinician inexperience, poor communication and logistical constraints. Addressing gaps in practice including standardized counselling stra tegies, pain control, cultural influence and child -friendly communication tools is crucial to prevent delays in diagnosis and treatment. This article explores key barriers and proposes actionable solutions in improving LP uptake among children in clinical setting s.